2023
DOI: 10.1108/compel-01-2023-0017
|View full text |Cite
|
Sign up to set email alerts
|

Fast numerical techniques for FE simulations in electrical capacitance tomography

Abstract: Purpose Nonlinear solution approaches for inverse problems require fast simulation techniques for the underlying sensing problem. In this work, the authors investigate finite element (FE) based sensor simulations for the inverse problem of electrical capacitance tomography. Two known computational bottlenecks are the assembly of the FE equation system as well as the computation of the Jacobian. Here, existing computation techniques like adjoint field approaches require additional simulations. This paper aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Hereby J is the Jacobian matrix, which holds the derivatives of the simulated measurements with respect to the elements of x. Efficient techniques for the computation of J are presented in [46]. Σ meas is a covariance matrix incorporating knowledge about the measurement noise.…”
Section: Formulation Of Prior Information For Flow Processesmentioning
confidence: 99%
“…Hereby J is the Jacobian matrix, which holds the derivatives of the simulated measurements with respect to the elements of x. Efficient techniques for the computation of J are presented in [46]. Σ meas is a covariance matrix incorporating knowledge about the measurement noise.…”
Section: Formulation Of Prior Information For Flow Processesmentioning
confidence: 99%
“…This section contains a summary of the fast numerical techniques presented in [38]. While the techniques were developed for the inverse problem of ECT, most aspects can be related to the complex-valued problems treated in this work.…”
Section: Fast Numerical Techniques For Symmetric Real-valued Problemsmentioning
confidence: 99%
“…In a previous study [38], our research group showed a set of fast numerical techniques for the solution of the inverse problem of ECT. This includes a fast technique for the assembly of the FE stiffness matrix K and, in particular, a set of techniques to evaluate matrix vector products with the Jacobian or its transpose without an explicit evaluation of J.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations